Does Financial Distress Risk Drive the Momentum Anomaly? - Agarwal, Vineet; Taffler, Richard J. (Wiley, 2008)
This paper brings together the evidence on two asset pricing anomalies-continuation of prior returns (momentum) and the market mispricing of distressed firms-using UK data. Our analysis demonstrates both these effects are driven by market underreaction to financial distress risk. In particular, we find momentum is proxying for distress risk, and is largely subsumed by our distress risk factor. We also find, as with US studies, no evidence that size and book-to-market (B/M) effects in stock returns are linked to financial distress.